International Regulatory Standards for the Qualitative Measurement of Deep Brain Stimulation in Clinical Research. (July 2022) - Stevens, I.; Gilbert, F.
Deep brain stimulation (DBS) has progressed to become a promising treatment modality for neurologic and psychiatric disorders like epilepsy and major depressive disorder due to its growing personalization. Despite evidence pointing to the benefits of DBS if tested on these personalized qualitative metrics, rather than randomized-control trial quantitative standards, the evaluation of these novel devices appears to be based on the latter. This study surveyed the presence of this trend in the national regulatory guidelines of the prominent DBS researching countries. It was found that two governing bodies, in the European Union and Australia, acknowledged the option for qualitative measures. These findings support further development of national regulatory guidelines, so the neuroscientific community developing these neurotechnologies can better understand the impact their treatments have on patients.